Growth response of leucaena embryogenic callus on embryo age differences and Auxin 2,4-Dichlorophenoxyacetic acid - Satria Julier Manpaki; Iwan Prihantoro; Panca Dewi M.H. Karti (Indonesian Center for Animal Research and Development (ICARD), 2018)
Leucaena (Leucaena leucocephala cv. Tarramba) is a source of protein from the legume family. Tarramba varieties able to adapt well in tropical area such as West Nusa Tenggara and East Nusa Tenggara. This study aimed to identify the growth response and embryogenic callus morphology of lamtoro (L. leucaena cv. Tarramba) in embryos different ages and auxin 2,4-D levels. This research was used explants derived from lamtoro (L. leucocephala cv. Tarramba) as much 400 explants. this study conducted of 16 treatments with two factors, the first factor is the provision of PGR 2,4-D concentration of 0.5 mg L-1, 1 mg L-1, 1.5 mg L-1 and 2 mg L-1. The second factor was the type of embryo such as mature embryo, cotyledon, heart, and pre-globular. Each treatment was repeated 25 replications. This study uses a randomized complete design (CRD) with two factor. Data were analyzed using analysis of variance and if there was significant difference, data were further analyzed using Duncan’s multiple range test. Analysis of variance showed that PGR 2,4-D at a concentration of 1.5 mg L-1 and the type of optimum embryo was mature embryo callus on parameters as height, diameter increment callus, and callus color scores were significantly different (P <0.05). callus texture parameter indicates results that are uniform throughout the treatment that was compact callus. Lamtoro plant embryogenic callus (L. leucocephala cv. Tarramba) indicate an optimal response at the concentration of PGR 2,4-D 1.5 mg L-1 and the type of embryo was mature embryo.